2015
DOI: 10.1073/pnas.1502032112
|View full text |Cite
|
Sign up to set email alerts
|

Triangulation of the neurocomputational architecture underpinning reading aloud

Abstract: The goal of cognitive neuroscience is to integrate cognitive models with knowledge about underlying neural machinery. This significant challenge was explored in relation to word reading, where sophisticated computational-cognitive models exist but have made limited contact with neural data. Using distortion-corrected functional MRI and dynamic causal modeling, we investigated the interactions between brain regions dedicated to orthographic, semantic, and phonological processing while participants read words al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
91
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 83 publications
(130 reference statements)
17
91
0
1
Order By: Relevance
“…A. Wilson et al, 2012; Woollams et al, 2007). This conforms with a recent proposal that the left lateral temporal neocortex plays an intermediary role in mapping between ventrally-situated transmodal conceptual knowledge representation and the frontal speech production network, subtending lexico-semantic processes such as reading and naming (Hoffman et al, 2015; Mehta et al, in press). However, the present study highlights a mid portion of the middle temporal gyrus that is considerably more posterior than the typical area of atrophy observed in svPPA and the region implicated in prior imaging studies of reading.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A. Wilson et al, 2012; Woollams et al, 2007). This conforms with a recent proposal that the left lateral temporal neocortex plays an intermediary role in mapping between ventrally-situated transmodal conceptual knowledge representation and the frontal speech production network, subtending lexico-semantic processes such as reading and naming (Hoffman et al, 2015; Mehta et al, in press). However, the present study highlights a mid portion of the middle temporal gyrus that is considerably more posterior than the typical area of atrophy observed in svPPA and the region implicated in prior imaging studies of reading.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are indicative of a critical role of the left-hemisphere lateral temporal cortex in exception word reading and are consistent with prior neuropsychological, computational modeling and functional imaging studies (Brambati, Ogar, Neuhaus, Miller, & Gorno-Tempini, 2009; Henry, Beeson, Alexander, & Rapcsak, 2012; Hoffman et al, 2015; Ueno, Saito, Rogers, & Lambon Ralph, 2011; M. A. Wilson et al, 2012; Woollams et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…From the VWFA, the ventral system extends into middle and inferior temporal gyrus (Tagamets, Novick, Chalmers, & Friedman, 2000), both of which have been linked to semantic processing (Fiebach et al, 2002; Simos et al, 2002). In addition, recent evidence has shown that the anterior temporal lobe (ATL) could also be an important semantic site in this pathway (Hoffman, Ralph, & Woollams, 2015). …”
Section: Introductionmentioning
confidence: 99%